정각화치성낭에서 발생한 구강편평세포암종: 증례보고 - 박우진; 김미선; 최소영; Woo-Jin Park; Mee-Seon Kim; So-Young Choi (대한구강악안면병리학회지, 2024)
Orthokeratinized odontogenic cysts are developmental cysts that occur in the jaw that account for approximately 7%–17% of all cysts in the jaws. Studies have shown that malignant transformation of odontogenic cysts most often occurs in inflammatory cysts, such as periapical cysts, but malignant transformation of orthokeratinized odontogenic cysts has also been reported. In this report, we present an uncommon case of squamous cell carcinoma arising from an orthokeratinized odontogenic cyst.